P249 Use of a point-of-care screening tool to identify depression and anxiety in patients with inflammatory bowel disease. (15th January 2020) - Karpin, J; Rodriguez, T; Traboulsi, C; Rai, V; Rubin, D
Abstract: Background: Depression and anxiety are comorbidities of inflammatory bowel disease (IBD). Recent guidelines from the ACG recommend screening for depression and anxiety in IBD patients, but the most effective and efficient way to do this is not established. We used a novel computerised adaptive testing technology to screen IBD patients for depression and anxiety and compared the screening results to disease activity. Methods: Consecutive patients at our tertiary IBD clinic were asked to complete the validated CAT-MH™ survey from Adaptive Testing Technologies (Chicago, IL). This tool is provided as a text or email link and takes 3–5 min to complete. We reviewed disease and patient characteristics. Categorical variables were assessed using Fisher's exact test. Clinical remission status was determined by the senior author, blinded to the CAT-MH™ results. Results: 134 patients (75 women, 112 Caucasian, 84 Crohn's disease) participated in the study, 85 of whom had no prior history of psychiatric disorders. We identified 51 patients with depression (46 mild, 3 moderate, 2 severe); 32/51 (62.7%) were previously undiagnosed. Thirty-six subjects tested positive for anxiety (24 mild, 10 moderate, 2 severe); 20/36 (55.6%) were previously undiagnosed. 2/134 patients were positive for suicidal ideation in the past month. Sex, race, type of IBD, surgical history, and number of discontinued medications were not significant (Table 1). Patients with active disease had a significantly greater relative risk for having depression (RR 2.26, 95% CI 1.50–3.39) and anxiety (RR 1.88, 95% CI 1.09–3.24) (Figure 1). Conclusion: We demonstrate the utility of a novel screening tool for depression and anxiety in IBD patients. Furthermore, we illustrate the positive association between clinically active disease status and the presence of depression and anxiety. Physicians should consider patients with clinically active IBD at risk for depression and anxiety and treat or refer them accordingly.